Freshwater Inflows to Texas Bays and Estuaries A Regional-Scale Review, Synthesis, and Recommendations - Montagna, Paul A.; Douglas, Audrey R.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
Estuaries are defined by mixing of river and sea water, thus freshwater inflow is a key driver of estuary ecosystem structure and function. While there is much concern about water quality, there is much less about water quantity. As water is diverted for human use, less is flowing to the coast, which threatens estuary ecosystems. Some jurisdictions are now setting inflow standards, but there is no consensus on how to identify how much freshwater an estuary needs. There is a climatic gradient along the northwestern Gulf of Mexico coast and estuaries vary from hydrologically positive to neutral to negative, and this makes the Texas coast the ideal place to study how ecological processes vary with freshwater inflow. An estuary comparison approach is used in this open access work to examine hydrology, circulation, salinity, nutrients, carbonate, dissolved oxygen, plankton, nekton, benthos, and habitat dynamics and responses across varying hydrological regimes.
Chapter 1. Introduction - History of Inflow Studies in Texas -- Chapter 2. Historical Perspective and Context of Freshwater Inflow Policy and Law in Texas -- Chapter 3. Climate Effects on Inflows -- Chapter 4. Hydrology, Circulation, and Salinity -- Chapter 5. Groundwater-Surface Water Interactions in the Coastal Zone -- Chapter 6. Influence of Inflows on Estuary Sediments -- Chapter 7. Nutrient-Phytoplankton Dynamics in Texas Estuaries -- Chapter 8. Physical and Biogeochemical Conditions and Trends in Texas Estuaries -- Chapter 9. Coastal Wetland Habitats in Texas -- Chapter 10. Submerged Aquatic Vegetation, Marshes, and Mangroves -- Chapter 11. Effect of Freshwater Inflow on Benthic Infauna -- Chapter 12. Effects of Climate-Driven Salinity Regimes on Oyster Disease Dynamics at Local and Regional Scales -- Chapter 13. Plankton Dynamics in Texas Estuaries -- Chapter 14. Nekton and Mobile Epibenthos -- Chapter 15. Nitrogen and Phosphorous Budgets for Texas Estuaries -- Chapter 16. Social and Economic Values of Environmental Flows to the Coast -- Chapter 17. Summary of Recommendations for the Future.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, described non-text content (images, graphs), bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Freshwater ecology; Marine ecology; Freshwater and Marine Ecology